Analisis Karakteristik Mineralogi dan Geokimia Berdasarkan Zona Profil Endapan Nikel Laterit (Studi Kasus: Blok X PT Ang and Fang Brother, Site Lalampu, Kecamatan Bahodopi, Kabupaten Morowali, Provinsi Sulawesi Tengah - Asran Ilyas; Agung Rian Pasolo; Sri Widodo (Universitas Muslim Indonesia, 2022)
Regionally, the study area is located in the Ophiolite Belt of East Sulawesi, particularly in the Tomata Formation (Tmpt), and is composed of igneous rock distribution in the Ultramafic Complex (Ku). The exposed of ultramafic rocks, caused the study area to contain elements of economic value such as nickel. The study aims to identify the constituent minerals, determine the abundance of elements and compounds, as well the correlation of major and minor elements and compounds based on the profile zone of laterite nickel deposits. Study data were in the form of soil and rock samples, and drilling data as many as 59 points. The mineral content of the study results was obtained based on the analysis of X-ray Diffraction and Petrography, while the univariate and bivariate statistical analysis was carried out on the drilling data. The results of the analysis obtained assemblages of minerals in the form of goethite, hematite, chlorite, and quartz in the limonite zone; antigorite, enstatite, chlorite, quartz, and magnetite in the saprolite zone; and lizardite, enstatite, spinel, and magnetite in the bedrock zone, with the bedrock type being serpentinized harzburgite. The results of the descriptive analysis showed the grade of major elements and compounds, which are Fe, SiO2, MgO, and Al, as well as minor elements, which are Ni, Cr, Co, Ca, and Mn which varied in each zone, where grade of SiO2, MgO, and Ca increased to the bottom of the profile, and the grade of Fe, Al, Cr, Mn, and Co decreased towards the bottom of the profile, while Ni increased to the saprolite zone. The results of the correlation of elements and compounds in the limonite zone are Cr vs Mn; SiO2 vs MgO and Ca; Ni vs Co and Cr; Fe vs Co positive is very strong to strong correlation, while Fe vs SiO2, MgO vs Al; Al vs Ni is strong negative correlation. Saprolite zone Fe vs Al, Cr, and Co; Cr vs Mn and Co; Mn vs Co; SiO2 vs MgO; Fe vs Mn; Al vs Cr, Mn, and Co were very strong to strong positive correlation, while Fe vs SiO2 and MgO; SiO2 vs Co; MgO vs Cr and Co; SiO2 vs Al, Cr, and Mn; MgO vs Al and Mn were very strong to strong negative correlation. Bedrock zones of Fe vs Cr, Mn, and Co; Cr vs Mn; Fe vs Al; Co vs Al, Cr, and Mn were very strong to strong positive correlation, while MgO vs Fe and Cr were strongly negative correlation.